Increased Enterococcus faecalis infection is associated with clinically active Crohn disease. Issue 39 (September 2016) - Zhou, Youlian; Chen, Huiting; He, Hanchang; Du, Yanlei; Hu, Jiaqi; Li, Yingfei; Li, Yuyuan; Zhou, Yongjian; Wang, Hong; Chen, Ye; Nie, Yuqiang
Abstract : Abstract: This study was performed to investigate the relationship between the abundance of pathogenic gut microbes in Chinese patients with inflammatory bowel disease (IBD) and disease severity. We collected clinical data and fecal samples from 47 therapy-naive Chinese patients with ulcerative colitis (UC), 67 patients with Crohn disease (CD), and 48 healthy volunteers. Bacteria levels of Fusobacterium species (spp), enterotoxigenic Bacteroides fragilis ( B fragilis ), enteropathogenic Escherichia coli ( E coli ), and Enterococcus faecalis ( E faecalis ) were assessed by quantitative real-time PCR (qRT-PCR). Spearman correlation coefficients were calculated to test associations between bacterial content and clinical parameters. Compared to healthy controls, the levels of both Fusobacterium spp and E faecalis were significantly increased in the feces of patients with IBD ( P < 0.01). B fragilis levels were higher ( P < 0.05) and E faecalis levels lower ( P < 0.05) in patients with CD compared to those with UC. Increased E faecalis colonization in CD associated positively with disease activity ( P = 0.015), Crohn disease activity index (CDAI; R = 0.3118, P = 0.0108), and fecal calprotectin ( P = 0.016). E faecalis and Fusobacterium spp are significantly enriched in patients with IBD, and increased E faecalis infection is associated with clinically active CD.